The Veil: A Phenomenon of Urban Society and Religious Identity - Surawan, Surawan; Najib Kailani; Muslim, Aziz (UIN Raden Mas Said Surakarta, 2023)
The veil, often perceived as a simple piece of clothing, holds complex meanings within urban society, serving as both a social phenomenon and a potent religious symbol. This article delves into the intricate dynamics of the veil within the context of contemporary urban life. It explores the dual nature of the veil, where it is not merely a garment but also a profound symbol of religious identity, modesty, and devotion. By examining the urban context, this research provides insights into how the veil is embraced, interpreted, and experienced by diverse communities residing in cities. The article discusses the complex social, cultural, and religious dynamics surrounding the veil and highlights its role in shaping personal and collective identities. Furthermore, it explores the challenges and debates faced by urban communities in accommodating the diversity of veiling practices and their implications for social cohesion and integration. This study offers valuable insights into the broader discourse on religious expression and cultural diversity within urban environments, emphasizing the need for a deeper understanding of the significance of the veil in contemporary society.